Efforts to Resolve Disputes in Murabahah Contracts in Sharia Financial Institutions - Trisnanda Rielta; Annisa Sonia Moniq Harahap; Fara Nazla; Dyna Varissa Indah Siregar; Putri Anggraini (ISNU Nine-Star Multidisciplinary Journal, 2025)
This study analyzes the concept and dispute resolution of murabahah contracts  in Indonesian Islamic financial institutions. The formulation of the research problem includes: (1) how the concept  of murabahah contracts  in Islamic financial institutions, and (2) how to resolve disputes that occur in murabahah contracts. The purpose of this study is to examine the concept, harmony, conditions, and mechanism of murabahah contracts based on the provisions in the Compilation of Sharia Economic Law (KHES), as well as the evaluation of dispute resolution based on sharia principles and positive Indonesian law. The method used is a normative method used with the analysis of primary legal materials (Law No. 21/2008 on Sharia Banking and KHES), and secondary legal materials in the form of literature, scientific articles, and fatwa DSN-MUI. Data was collected through document studies and literature review, then analyzed descriptively and analytically using a qualitative approach. The results of the study show that the murabahah contract  is mandatory to meet the principles of transparency, honesty, justice, harmony and conditions in accordance with sharia principles and in accordance with the provisions of positive Indonesian law. Disputes generally arise due to customer default, resolved through deliberation, contract conversion, the National Sharia Arbitration Board, or the Religious Court in accordance with KHES and DSN-MUI fatwa. This study recommends strengthening regulations, legal protection, and socialization of sharia principles to foster a sense of trust in the public towards the Islamic financial mechanism in Indonesia.